Comparison of camera calibration parameters using Photomodeler and Australis - Abd. Rahman, Fazli; Setan, Halim; Chong, Albert K.; Majid, Zulkepli; Ahmad, Anuar (2004)
Photomodeler and Australis are two common photogrammetry software that provide camera calibration, and the camera calibration parameters. Each software uses different calibration approach (circular point detection in Australis and intersection of lines in Photomodeler). This paper compares the calibration parameters of Canon IXUS S400 PowerShot digital camera using both Photomodeler and Australis. During calibration, several images were taken with the same camera setting and the distance from the camera to the calibration field was 0.8 meter. All seven camera calibration parameters obtained from the software are compared and tested for statistical significance. The seven parameters are focal length, xp, yp, radial distortion ( K1 and K2 ) and tangential distortion ( P1 and P2 ).